2012
DOI: 10.3122/jabfm.2012.03.110101
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides as a Cause of Fever of Unknown Origin

Abstract: Strongyloides is endemic in parts of the United States. Most often it is asymptomatic but it has a wide range of clinical presentations. Because of the unusual capacity of strongyloides for autoinfection, it can cause hyperinfection, when it effects the pulmonary and gastrointestinal systems, or disseminated infection, when other organs are involved. Both hyperinfection and disseminated strongyloides usually occur in immunosuppressed patients. We report a case of hyperinfection with strongyloides in a man pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…A total of 146 papers was reviewed with nine meeting all criteria (Table ) . Most patients were male (88.9%) with a median age of 48 years (range 24–79 years).…”
Section: Case Reports Of Shs In Immunocompetent Patientsmentioning
confidence: 99%
“…A total of 146 papers was reviewed with nine meeting all criteria (Table ) . Most patients were male (88.9%) with a median age of 48 years (range 24–79 years).…”
Section: Case Reports Of Shs In Immunocompetent Patientsmentioning
confidence: 99%
“…stercoralis infections are often mild and associated with few or no symptoms. However, during the lung migratory phase, filariform larvae may induce inflammatory reactions, such as pneumonitis, bronchopneumonia, and pulmonary hemorrhage, including fever, 16 productive cough, wheezes, dyspnea hemoptysis, and bronchospasm. [17][18][19] Pulmonary symptoms, including dyspnea, cough, and sputum discharge, were recorded in 15.7% of S. stercoralis-infected cases.…”
Section: Pulmonary Strongyloidiasismentioning
confidence: 99%
“…Lee and Cheong, 13 2 family physicians from Korea, provide an interesting report of their endoscopic repair of a perforation that occurred during a routine screening colonoscopy. Mounsey et al, 14 family physicians from the United States, discuss a case of strongyloides causing a fever of unknown origin in an immunocompetent man, reviewing both the common and uncommon forms (such as this one) of helminth infection. Brown et al 15 found…”
mentioning
confidence: 99%